Paweł Grochowski. Chrystian: biskup Prus 1216–1245 i misja pruska jego czasów. Górna Grupa: Wydawnictwo Verbinum, 2018. 500 pp., 34 photographs, 22 drawings. ISBN: 978-83-7192-552-8. - Dygo, Marian (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2020)
Paweł Grochowski. Chrystian: biskup Prus 1216–1245 i misja pruska jego czasów. Górna Grupa: Wydawnictwo Verbinum, 2018. 500 pp., 34 photographs, 22 drawings. ISBN: 978-83-7192-552-8.